Human Galectin-1 in Multiple Cancers: A Privileged Molecular Target in Oncology - Goud, Nerella S.; Bhattacharya, Ahana (Mini Reviews in Medicinal Chemistry, 2021)
Galectin-1 (Gal-1), a 14kDa carbohydrate-binding protein of the galectin family found in humans, affects intracellular signaling pathways upon interaction with β-galactosides on cell-surface, cytosol, and nucleus. The structural information reveals that it consists of a monovalent dimer composed of subunits with one Carbohydrate Recognition Domain (CRD), which is the main active site to interact with various glycoproteins, and carbohydrates in the body to regulate cellular functions. Gal-1 contributes towards different events associated with cancer biology, including tumor transformation, cell cycle regulation, apoptosis, cell adhesion, migration, and inflammation. The extracellular existence and function of Gal-1 have been well-established, and it is known to express in many tumor types, including astrocytoma, melanoma, prostate, colon, bladder, and ovarian carcinomas, etc. Several studies suggested the upregulation of Gal-1 levels in multiple cancer cells. Thus, Gal-1 is a promising molecular target for the development of new therapeutic tools. The present review focuses on the functions of Gal-1 in tumor progression in multiple cancers and its structural insights.
Keywords: cancer